(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The main concern of this work is to make a complete study of the palaeohispanic epigraphy, discovered until now at the Iberian Murcian site Coimbra del Barrancho Ancho (Jumilla), as well as the first philological study of the lead plaque, after the restoration.